Conformity of annual reports to an integrated reporting framework: ASE listed companies - Ghada A. Altarawneh; Asma'a Omar Al-Halalmeh (International Journal of Financial Studies, 2020)
The objectives of this study are to determine the level of conformity between Current Issued Reports (CIRs) and Integrated Report (IR) elements of the Amman Stocks Exchange (ASE) listed companies, as well as to determine whether the investigated corporate characteristics (size, age, quality assurance (QA), earning per share (EPS), industry type, foreign ownership (FO) of these companies have any impact on the conformability of CIRs. It is worth mentioning that (QA), and (EPS), have never been examined by looking at its association with corporate disclosures, and IR in particular. Based on adoption of the IR framework and using the method of content analysis, corporate annual reports and other stand-alone reports of 82 companies in 2017 and 2018 within the financial, industrial, and services sectors, were chosen for this study. The findings of the study provide an answer to the research question and show that sectors vary in their levels of conformity. It reveals that the service sector shows the lowest conformability compared to other sectors, whereas the financial firms conform 65%, followed by the industrial sector. It also finds a positive association between CIRs conformability and variables of size, age of company and quality assurance. However, EPS, FO and type of industry were found to have no impact on the conformability of CIRs to the IR framework. This study has contributed to IR research, which, as a field, has previously received very little recognition among scholars in Jordan. Moreover, IR still does not exist in Jordan's business practices.
Keywords: M41; M14; H83; 330; accounting disclosure; integrated reporting; international integrated reporting council; content elements; content analysis; ASE